Mathematical Modeling of Thermomechanical Stresses of Multilayer Erosion-Resistant Electrode Coatings of Magnetically Controlled MEMS. Issue 1753 (3rd March 2015) - Karabanov, Sergey; Suvorov, Dmitriy; Gololobov, Gennady; Slivkin, Evgeny; Tarabrin, Dmitry
ABSTRACT: The paper presents the results of numerical modeling of thermomechanical stresses and thermal fields for conditions of erosion-resistant electrode coatings of magnetically controlled MEMS switches with W-Ti-Cu structure at local temperature and electric current influence in axially symmetrical approximation. It is shown that the introduction of titan interlayer (30-100 nm) in the coating with W-Ti-Cu structure results in considerable (more than two times) decrease of internal thermomechanical stresses between layers that increases coating resistance to delamination. It is established that there is an optimum value of Ti layer thickness at which the minimum thermomechanical stresses are provided.